Assessment of Cochlear Trauma During Cochlear Implantation Using Electrocochleography and Cone Beam Computed Tomography. Issue 5 (June 2016) - Dalbert, Adrian; Huber, Alexander; Veraguth, Dorothe; Roosli, Christof; Pfiffner, Flurin
Abstract : Objective: To assess cochlear trauma during cochlear implantation by electrocochleography (ECoG) and cone beam computed tomography (CBCT) and to correlate intraoperative cochlear trauma with postoperative loss of residual hearing. Methods: ECoG recordings to tone bursts at 250, 500, 750, and 1000 Hz and click stimuli were recorded before and after insertion of the cochlear implant electrode array, using an extracochlear recording electrode. CBCTs were conducted within 6 weeks after surgery. Changes of intraoperative ECoG recordings and CBCT findings were correlated with postoperative threshold shifts in pure-tone audiograms. Results: Fourteen subjects were included. In three subjects a decrease of low-frequency ECoG responses at 250, 500, 750, and 1000 Hz occurred after insertion of the electrode array. This was associated with no or minimal residual hearing 4 weeks after surgery. ECoG responses to click stimuli were present in six subjects and showed a decrease after insertion of the electrode array in three. This was associated with a mean hearing loss of 21 dB in postoperative pure-tone audiograms. Scalar dislocation of the electrode array was assumed in one subject because of CBCT findings and correlated with a decrease of low-frequency ECoG responses and a complete loss of residual hearing. Conclusion: Hearing loss of ≤11 dB is not associated with detectable decrease in ECoG recordings during cochlear implantation. However, in a majority of patients with threshold shifts of >11 dB or complete hearing loss, an intraoperative decrease of high- or low-frequency ECoG signals occurs, suggesting acute cochlear trauma.